Utility of Psychometric and Dynamic Assessments for Identifying Cognitive Characteristics of Twice-Exceptional Students - Al-Hroub, Anies (Frontiers in Psychology, 2021)
The purpose of this research was to examine the utility of psychometric and dynamic assessment for the identification of a twice-exceptional (2E) group of students who showed both high mathematical abilities and specific learning disabilities. Of a population of 800 students, 30 (14 boys and 16 girls) ages 10 to 12 years were selected and identified as twice-exceptional at three public elementary schools in Amman, the capital of Jordan. The researcher used a combination of three psychometric tests and one dynamic math assessment tool to recognize the cognitive and perceptual characteristics, strengths, and difficulties among students. Both psychometric and dynamic assessment models were found essential and complementary to identify cognitive and perceptual factors of twice-exceptional children. The findings indicated that dynamic assessment significantly influenced students’ mathematical learning skills. The results were reported and discussed.